Implementing Mindfulness Practices With Parents of Young Children in a Low-Socioeconomic Status Neighborhood - Andrew Roach; Josephine Mhende; Brian Barger; Douglas Roberts (Georgia Southern University, 2019)
Background: The purpose of this study was to investigate whether instruction in mindfulness practices would results in improved self-reported mindfulness and reduced depression, anxiety, and family stress in parents of young children living in a low socioeconomic status (SES) neighborhood. Methods: The study utilized a pretest-posttest group design to evaluate the effectiveness of the Mindfulness Ambassador Council-Interactive curriculum with attendees in a parent support program. Participants (n=15) were recruited from families with young children who received support from a community-based organization in one low-SES neighborhood in Atlanta. Mental health assessments, measures of family stress and parenting competency, and a demographic questionnaire with non-identifying questions were administered to all participants during the first and last session of the 8-week mindfulness program. Results: Participants reported increased mindfulness and decreased levels of anxiety and depression. Parent reports of family stressors were relatively stable across the two time points, while self-reported parenting competence decreased. Discussion: Based on the parents' reports of program acceptability and the impact on their well-being, mindfulness training appears to be a promising strategy for addressing the stressors experienced by parents of young children. Keywords: Parenting, young children, mindfulness, stress, depression, anxiety